The effect of disinfectants on fertility of male mice (Mus musculus l.) - Khofifah, Nur; Hanizar, Evi; Zuhro, Fatimatuz (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2025)
Since the outbreak of COVID-19, disinfectants have not only been used in health facilities, but they have also spread to households. The problem was that people often use disinfectant formulas that did not complied with health institutions guidelines. This study aims was to evaluate the effects of two types of disinfectants on the fertility, parameters of male mice, namely sperm concentration, motility and morphology. This was a true experimental study, with three treatment groups, namely the disinfectant type Alkyl Dimethyl Benzyl Ammonium Chloride (ADBAC) with a concentration of 10 mL/L, pine oil with a concentration of 30 mL/L, and control. The dose of each disinfectant was determined from the initial LD50 study. 20 mL of each disinfectant was sprayed on the cage twice a day in the absence of animals. The animals used were four week old male Mus musculus and were treated for 5 weeks. The parameters observed consisted of sperm concentration, motility, and morphology. All data were analyzed by one way Anova and Duncan's advanced test. The analysis results showed that the disinfectant had no effect on sperm concentration but instead had a negative effect on sperm motility and morphology. Both types of disinfectants reduced the progressive motility of sperm, while ADBAC produced more abnormal sperm morphology than pine oil. This condition is in accordance with other research that sperm motility is closely related to sperm morphology. The results of this study add to the evidence that disinfectants have a negative effect on male fertility parameters, namely sperm quality. The use of disinfectants for long periods also requires attention.